AUTHOR’S QUALITIES ESSENTIAL FOR A GOOD SCIENTIFIC PUBLICATION - Shamim, Thorakkal (Journal of Ayub Medical College Abbottabad, 2010)
Medical publications are an important means to gain recognition as experts in a particular field at national and international levels. Publications will leads to benefits such as invitations to lecture at scientific meetings and refresher courses, appointments as consultants to external agencies, expert panels and advisory boards, and to reviewer and editorial boards of journals.1 I would like to mention the qualities of a good author for an article to get published in an indexed medical journal (Table-1). Table-1: Author’s qualities essential for a good scientific publication Genuine interest to publish an article Positive attitude Sufficient time management Accept criticisms from the reviewers Good and peaceful mind set Stress less working place Patience Confidence Authors should have genuine interest to publish an article. If he is not interested and compelled by higher authorities (Head of the Department) to publish an article, he will come up with article with plagiarism. He should take positive attitude so that his article will get published. He should have sufficient time to write the article, critically evaluating the content, revising the article and proof reading the article. He should accept criticisms from the reviewers. He should have good and peaceful mind set and stress less working place is an essential requisite for a good author. He should have good patience to write the article, critically evaluating the content, waiting for the review period, revising the article and proof reading the article. He should have self confidence that his article will get published. It is important for authors to be aware of these qualities before submitting an article.